Interdisciplinarity and pluralism of methodological approaches in sociological research - Zborovskii, Garold E. (Journal of the Belarusian State University. Sociology, 2019)
The article proves the scientific expediency of using a number of disciplinary and interdisciplinary methodological approaches to theoretical and empirical sociological research on the basis of the application of the principle of their pluralism. Structural elements of scientific sociological research are characterized. Pluralism of approaches in sociology is viewed as an integral part of the methodology and program of sociological empirical and theoretical research, as a scientific, practical and socio-political problems. Considerable attention is paid to the analysis of the correlation of various methodological approaches in sociology. The problem of compiling a matrix of disciplinary and interdisciplinary approaches and its approbation in the process of studying specific social phenomena and processes is discussed. A question is raised about the use in recent years of socio-humanitarian studies of natural-scientific approaches, provided that they are methodologically sound.